Стихи о природе: [для среднего школьного возраста] (Библиотечка школьника, 2015)
Экземпляры: Ф-5 (20161007) / Инвентарный номер: 50190 / Цена: 67.00 / Сис.шифр: Сб / Авт.знак: С 80 / ГРНТИ: 17.82 / ББК: 84 (2Рос=Рус) 6